2017
DOI: 10.1111/aos.13403
|View full text |Cite
|
Sign up to set email alerts
|

Time spent in outdoor activities in relation to myopia prevention and control: a meta‐analysis and systematic review

Abstract: Outdoor time is considered to reduce the risk of developing myopia. The purpose is to evaluate the evidence for association between time outdoors and (1) risk of onset of myopia (incident/prevalent myopia); (2) risk of a myopic shift in refractive error and c) risk of progression in myopes only. A systematic review followed by a meta‐analysis and a dose–response analysis of relevant evidence from literature was conducted. PubMed, EMBASE and the Cochrane Library were searched for relevant papers. Of the 51 arti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
393
3
11

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 423 publications
(419 citation statements)
references
References 80 publications
(253 reference statements)
12
393
3
11
Order By: Relevance
“…We believe as evidence suggests that time outdoors remain the most important factor (Xiong et al. ). There is, however, an inherent confusion in the topic due to the close relation between PA and outdoor activity.…”
Section: Discussionmentioning
confidence: 80%
“…We believe as evidence suggests that time outdoors remain the most important factor (Xiong et al. ). There is, however, an inherent confusion in the topic due to the close relation between PA and outdoor activity.…”
Section: Discussionmentioning
confidence: 80%
“…The majority (almost 90 per cent) of respondents also considered increasing the time spent outdoors to be beneficial for reducing myopia progression. While ensuring adequate (greater than two hours/day) outdoor time is a protective factor for myopia development, its potential efficacy as an ‘intervention’ for reducing myopia progression is less certain . As summarised in a systematic review and meta‐analysis by Xiong et al, most studies to date have not shown clear benefit.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have observed that increased ambient illumination is protective for FDM in animal models, and time outdoors is protective for myopia in children . The mechanisms of the protective effects of light are unknown, and might include both neurochemical factors, such as alterations in melanopsin and dopamine cascades, and optical factors, such as miosis‐induced increased depth of field, a flatter dioptric scene, and spectral distribution of sunlight and chromatic cues.…”
Section: Spectral and Temporal Characteristics Of Lightmentioning
confidence: 99%